MEMBACA KOMIK CRAYON SHINCHAN DENGAN WACANA POSMODERNISME - Purbani, Widyastuti (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
This article is concerned with a heated controversy about the Crayon Synchancomic serial and aims at producing an alternative reading view using a postmodernperspective. Situating the text concerned in the discourse of postmodernism,referring especially to its view on the fall of grand narratives, the use of parody andintertextuality, the way it posits readers, the aestheticization of ordinary life, andthe way it sees the human body and sexuality, we could render more understandingand fair value judgment and therefore restrain our prejudice towards this text.Keywords: postmodernism, metanarrative, parodyA.